Identifying Spatial Efficiency-Equity Trade-offs in Territorial Development Policies : Evidence from Uganda - Lall, Somik V.; Schroeder, Elizabeth; Schmidt, Emily (Taylor and Francis, 2015)
We contribute to the debate on the spatial allocation of infrastructure investments by examining where these investments generate the highest economic return (‘spatial efficiency’), and identifying trade-offs when infrastructure coverage is made more equitable across regions (‘spatial equity’). We estimate models of firm location choice in Uganda, drawing on insights from the new economic geography literature. The main findings show that manufacturing firms gain from being in areas that offer a diverse mix of economic activities. Public infrastructure investments in other locations are likely to attract fewer private investors, and will pose a spatial efficiency–equity trade-off.